2008
DOI: 10.1002/jmv.21209
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human metapneumovirus among hospitalized children younger than 1 year in Catalonia, Spain

Abstract: Human metapneumovirus was discovered recently respiratory virus implicated in both upper and lower respiratory tract infection. In children, the clinical symptoms of human metapneumovirus are similar to those produced by respiratory syncytial virus, ranging from mild to severe diseases such as bronchiolitis and pneumonia. The aim of the present study was to describe the prevalence of human metapneumovirus and other common respiratory viruses among admitted to hospital infants. From January 2006 to June 2006, 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 57 publications
1
13
1
Order By: Relevance
“…The observation of only one circulating lineage among the study population was also mentioned in other studies. In Spain,31 Italy32 and China33,34 circulation of HMPV A2 lineage was reported. However, a number of studies have indicated that circulating predominant strains may vary on an annual basis and that their replacement may occur, on average, every 1–3 years 35,36…”
Section: Discussionmentioning
confidence: 99%
“…The observation of only one circulating lineage among the study population was also mentioned in other studies. In Spain,31 Italy32 and China33,34 circulation of HMPV A2 lineage was reported. However, a number of studies have indicated that circulating predominant strains may vary on an annual basis and that their replacement may occur, on average, every 1–3 years 35,36…”
Section: Discussionmentioning
confidence: 99%
“…In immunocompetent individuals, rhinoviral clearance after symptomatic infection is rapid (average 1-3 weeks). 18 Pneumonia was diagnosed in 10% of children admitted with acute human metapneumovirus respiratory infection, [63][64][65][66] with the highest prevalence (44%) in infants younger than 12 months. 66 It has also been recorded in 11-75% of children with human bocavirus infection.…”
Section: Paediatric Studiesmentioning
confidence: 99%
“…18 Pneumonia was diagnosed in 10% of children admitted with acute human metapneumovirus respiratory infection, [63][64][65][66] with the highest prevalence (44%) in infants younger than 12 months. 66 It has also been recorded in 11-75% of children with human bocavirus infection. 67 In a study from Thailand of infants younger than 5 years admitted with pneumonia, human bocavirus was the third most prevalent agent detected, after rhinovirus and respiratory syncytial virus, accounting for 12% of all cases.…”
Section: Paediatric Studiesmentioning
confidence: 99%
“…Respiratory viruses are a major cause of influenza-like illness(ILI) symptoms in children and adults, leading to substantial morbidity and mortality each year [1][2][3][4][5]. The complications of ILI symptoms may occur in young children (< 1 year old) and elderly people (> 65 years old), even though ILI symptoms is most often self-limited and restrained to the upper respiratory tract [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…brief study schedule at every visit. Item need to be performed during the visit 1 Sex, date of birth, age, contact address and phone number 2 Include present illness, past history taking3 Frequency of ILI symptom onset, severity of ILI symptoms, and duration of ILI symptoms4 Blood test (WBC, RBC, hemoglobin, hematocrit, platelets count, AST, ALT, ALP, gamma-GTP, albumin, BUN, creatinine, glucose, total bilirubin, total protein), urine test (specific gravity, pH, protein, ketone, glucose, bilirubin, urobilinogen, nitrite, microscopic (RBC, WBC))…”
mentioning
confidence: 99%